Analysis of correlation between scores of performance factors in cross-country skiers obtained by various methods of determination of weights in expert modelling - Černohorski, Branimir (Kinesiologia Slovenica, 2005)
In the research, two universal reduced models of potential competition performance in cross-country skiing were constructed. The MMPS model covers the motor, morphological, psychological and sociological subspace of the psychosomatic status of competitors, while in the MFMPS model, a functional subspace has also been added. Within both models, we wanted to establish a degree of correlation between the scores of some important levels of psychosomatic status obtained by the SMMS procedure of expert modelling by the method of dependent and independent determination of weights. On a sample of 14 competitors (older juniors) the agreement between the scores of variables obtained by the two different methods of weight determination was established. We found that the final score of both models (URMPU) is highly corelated with their subspaces, except with the sociological one. The degree of interrelations between individual subspaces varies; however, the highest correlation exist between the motor and psychological subspaces in the method of dependent determination of weights, while the utility of the method of independent determination of weights is larger.
Keywords: ekspertno modeliranje; metodologija; raziskave; smučarski tek; tekmovalna uspešnost